Domain- and trimester-specific effect of prenatal phthalate exposure on preschooler cognitive development in the Ma'anshan Birth Cohort (MABC) study. (September 2020) - Zhu, Yuan-duo; Wu, Xiao-Yan; Yan, Shuang-qin; Huang, Kun; Tong, Juan; Gao, Hui; Xie, Yang; Tao, Shu-man; Ding, Peng; Zhu, Peng; Tao, Fang-biao
Highlights: We evaluated the effect of prenatal phthalate exposure on children cognitive development by repeated measure analysis. The first trimester might be the most critical period of cognitive development in term of exposure to phthalate. VCI and VSI might be more susceptible to phthalates exposure than other domains. A gender-specific effect may exist between prenatal phthalates exposure and IQ. Abstract: Background: Phthalates are a group of heavily produced endocrine disruptors that are widely used in personal care products, food packaging, building materials, and medical device. Few epidemiological studies have examined the effect of repeated prenatal exposure to multiple phthalates on preschooler cognitive development. Objectives: This study aimed to examine the association between prenatal phthalate exposure measured at multiple time points and the intelligent quotient (IQ) scores of preschoolers, and to further identify the critical windows and specific intelligence domains in which phthalate exposure would affect preschooler cognitive development. Methods: The current study was based on the Ma'anshan Birth Cohort (MABC) study. Seven phthalate metabolites were measured in 2128 maternal urine samples collected during the first, second, and third trimesters of pregnancy. The IQ score of preschool-aged children were assessed with the Chinese version of the Wechsler Preschool and Primary Scale of Intelligence, Fourth edition (WPPSI-Ⅳ CN). Linear mixed models (LMMs) were used to assess the longitudinal effects of repeated prenatal phthalate exposure on children's IQ score. Multiple linear regression models were fitted to determine whether critical window phthalate exposure would affect cognitive development of children. Results: Overall, the repeated measures analysis indicated that the verbal comprehension index (VCI), visual space index (VSI) and full-scale intelligence quotient (FSIQ) decreased by 0.30 (95% CI: −0.60, 0; p = 0.05), 0.32 (95% CI: −0.62, −0.01; p = 0.04), and 0.31 (95% CI:-0.57, −0.04; p = 0.02) points, respectively, with each ln-transformed increase in the metabolite concentration of MBP. The fluid reasoning index (FRI) and processing speed index (PSI) increased by 0.30 (95% CI: 0.07, 0.54; p = 0.01) and 0.28 (95% CI: 0.06, 0.51; p = 0.01) points, respectively, with each ln-concentration increase in MEP. Trimester-specific regression models stratified by the sample collection time during pregnancy generated consistent results. In the first trimester, each ln-transformed MBP increase was associated with reductions in VCI, VSI and FSIQ of 0.56 (95% CI:-1.09, −0.02; p = 0.04), 0.60 (95% CI:-1.15, −0.05; p = 0.03) and 0.49 (95% CI:-0.97, −0.01; p = 0.04) points, respectively. In the third trimester, we observed that only MBzP exposure was associated with an increase in VCI (β: 0.48, 95% CI: 0.03, 0.92; p = 0.04). The gender-stratified analyses revealed that boys drove these associations. Conclusions: Our results suggest that prenatal phthalate exposure impairs the cognitive development of preschoolers. The first trimester of pregnancy might be the most vulnerable period in terms of neurotoxicitydue to phthalate exposure. These findings warrant further confirmation.